Endoscopy‐Assisted Transoral Approach to Resect Parapharyngeal Space Tumors: A Systematic Review and Meta‐Analysis. (22nd February 2021) - Chen, Huihong; He, Zhiying; Li, Guo; Liu, Chao; Zhang, Diekuo; Huang, Donghai; Xie, Changning; Jiang, Weihong; Qiu, Yuanzheng; Zhang, Xin; Liu, Yong
Abstract: Objectives: By comparing the endoscopy‐assisted transoral approach (EATA) with external approaches (EAs) for the resection of parapharyngeal space tumors (PPSTs), we determined whether the EATA has advantages in terms of operation time, intraoperative bleeding volume, postoperative hospitalization, drainage volume, and complications. At the same time, we summarized the surgical indications for the EATA. Methods: Systematic literature retrieval was performed in the PubMed, Web of Science, Embase, CNKI, Wanfang, and CQVIP databases up to February 2020. We calculated the mean difference (MD) with a 95% confidence interval (CI) for continuous outcomes and pooled odds ratio (OR) with 95% CI for dichotomous outcomes. The measured outcomes were operative time, bleeding volume, postoperative hospitalization, drainage volume, and complications. Results: Seven studies involving 318 patients were eligible. Of these patients, 145 patients underwent EATA and 173 patients underwent EA surgery. All the former tumors were benign and located medial or anteromedial to the carotid sheath except for the unrecorded tumors. Compared with EAs, the EATA significantly shortened the operation time (MD = −5.56 min, 95% CI: −9.58 to −1.55), shrank the bleeding volume (MD = −89.02 ml, 95% CI: −126.16 to −51.88), shortened the postoperative hospitalization (MD = −2.44 days, 95% CI: −3.37 to −1.51), reduced the drainage volume (MD = −32.97 ml, 95% CI: −36.24 to −29.70), and lowered the incidence of complications (OR = 0.30, 95% CI: 0.16 to 0.59). Conclusion: As for PPSTs, with an appropriate and precise patient selection, the EATA is a safe, effective, minimally invasive, and aesthetic surgical modality. Laryngoscope, 131:2246–2253, 2021